Social Problems in India: Focus on Gender Inequality: Progress and Challenges in Addressing Gender Inequality in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Problems are not new phenomena to India. Gender inequality in India refers to socially constructed differences between men and women in India that systematically empower one group to detriment of the other. Gender inequalities include unequal rights, responsibilities, and opportunities for Indian women and translate to poor health status, educational attainment, and economic status compared to men. Most notably, is the lack of opportunity for many girls to be born due to sex-selective abortions and shorter lifespan due to neglect as evidence in India’s highly skewed child sex ratio (under age 6) of 919 girls per 1,000 boys. Despite gains in economic development, India performs poorly on global measures of gender inequality and in 2012, fell behind all other Asian countries except Afghanistan on the UNDP Gender Inequality Index, ranking 132nd out of 148 countries. Women in India are at a particular disadvantage due to gender based violence and limited access to resources, place men at a disadvantage. However, when India’s population is examined as a whole, women are at a disadvantage in several important ways. Since its independence, India has made significant strides in addressing gender inequalities, especially in the areas of political participation, education, and legal rights. Policies and legal reforms to address gender inequalities have been pursued by the government of India.